2004
DOI: 10.1002/biof.5520220140
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐adipogenic effects of Garcinia extract on the lipid droplet accumulation and the expression of transcription factor

Abstract: Garcinia extract was used as a potential anti-obesity agent. In this study, we found that Garcinia extract inhibits the cytoplasmic lipid accumulation as well as adipogenic differentiation of preadipocytes. The mechanisms that regulate the inhibition of insulin-induced differentiation by Garcinia extracts include the inhibition of expression of the early adipogenic transcription factor, CCAAT element binding protein (C/EBP)alpha that regulate adipogenesis. These results suggest that the specific targets of Gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 9 publications
1
36
0
1
Order By: Relevance
“…The previous study reported that the Garcinia cambogia extracts inhibits lipid droplet accumulation in fat cells without affecting adipose conversion in 3T3-L1 cells [67]. In addition, Kim et al reported that Garcinia cambogia extracts inhibits the cytoplasmic lipid droplet accumulation as well as adipogenic differentiation of pre-adipocytes [68]. Consistent with the reduction of lipid droplet, our results showed that (-)-HCA treated significantly decreased the triglyceride content in primary chicken hepatocytes.…”
Section: Discussionsupporting
confidence: 80%
“…The previous study reported that the Garcinia cambogia extracts inhibits lipid droplet accumulation in fat cells without affecting adipose conversion in 3T3-L1 cells [67]. In addition, Kim et al reported that Garcinia cambogia extracts inhibits the cytoplasmic lipid droplet accumulation as well as adipogenic differentiation of pre-adipocytes [68]. Consistent with the reduction of lipid droplet, our results showed that (-)-HCA treated significantly decreased the triglyceride content in primary chicken hepatocytes.…”
Section: Discussionsupporting
confidence: 80%
“…These results are in agreement with the previous observation by other investigators that the inhibitory effect of the Garcinia cambogia extract against the insulin-induced differentiation of 3T3-L1 cells targeted the adipogenic transcription factor, C/ EBP. 45) Furthermore, the result that the expression of the TNF gene, which was up-regulated by HFD, was down-regulated again by the Garcinia cambogia extract supplemented to HFD corresponds well with the dietinduced changes in the expression of such other genes as PPAR2, C/EBP, and SREBP1c. Therefore, the Garcinia cambogia extract appears to have modulated the expression of a critical nuclear transcription factor that can trigger the entire process of adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 57%
“…Although we did not measure energy expenditure, but an increasing in feed intake provides indirect evidence for that rats supplemental with Garcinia Cambogia extracts were less efficient in using the food energy for the accretion of body mass, which suggests that energy expenditure was increased. Previous studies also reported that the Garcinia Cambogia extracts could remarkably reduce body weight gain, visceral fat accumulation, and serum lipid concentration in high-fat diet-induced obesity rats (Kim et al, 2008;Kim et al, 2004).…”
Section: Numerous Studies Have Shown An Association Between Garciniamentioning
confidence: 81%
“…This observation concurs with the finding of Kim et al (Kim et al, 2007), who reported that Garcinia Cambogia extracts could reduce the accumulation of visceral fat mass and triglyceride content in rats rendered obese by a high fat diet. As a weight loss agent, many studies had reported that (-)-HCA, the principal acid and the major active ingredient of Garcinia Cambogia extracts, safely promote weight loss in laboratory animals (Kang et al, 2007;Kim et al 2004) and humans (Kim et al, 2011;Márquez, 2012), and suggested food intake regulation may be a major mechanism of weight loss by Garcinia Cambogia extracts-induced (Louter-van de Haar et al, 2005). Present study showed that supplemental with median and high dose of Garcinia Cambogia extracts could increase the average daily feed intake was observed in rats under fed high-fat diet.…”
Section: Numerous Studies Have Shown An Association Between Garciniamentioning
confidence: 99%